Strategi Pemasaran dalam Menarik Minat Konsumen Ditinjau dari Etika Bisnis Islam : (Studi Pada Apotek di Wilayah Kerja Puskesmas Talang Pamekasan) - Anis Sulalah (Kariman: Jurnal Pendidikan Keislaman, 2023)
The implementation of marketing strategies within the company is very influential in the performance of the company concerned. The success or failure of a company is largely determined by the marketing strategy it uses. In terms of developing and implementing a marketing strategy there are several stages that must be determined, one of which is planning a marketing mix consisting of four main elements, namely product, price, distribution/place, and promotion. . Meanwhile, Islamic business ethics are morals in doing business in accordance with Islamic values, so that in conducting business there is no need to worry about fraudulent transactions. Doing business in the pharmaceutical sector is still believed to be a form of economic business that has good prospects. Even in a crisis, this business will remain stable because medicine is a mandatory requirement that must be met by people who are sick. Even so, it is possible that currently there are many pharmacies that are out of business where this is due to the inability of a seller to attract consumer interest and maintain it.